Effects of Cyclic Chronic Heat Stress on the Expression of Nutrient Transporters in the Jejunum of Modern Broilers and Their Ancestor Wild Jungle Fowl - Abdelli, Nedra; Ramser, Alison; Greene, Elizabeth S.; Beer, Lesleigh; Tabler, Travis W.; Orlowski, Sara K.; Pérez, José Francisco; Solà-Oriol, David; Anthony, Nicholas B.; Dridi, Sami (Frontiers in Physiology, 2021)
Heat stress (HS) has been reported to disrupt nutrient digestion and absorption in broilers. These effects may be more prominent in fast-growing chickens due to their high metabolic activity. However, the underlying molecular mechanisms are not yet fully elucidated. Hence, the current study aimed to evaluate the effect of chronic HS on jejunal nutrient transport in slow- (Athens Canadian Random Bred, ACRB from 1950), moderate- (The 1995 random bred, 95RAN), rapid- (modern broilers, modern random bred, MRB) growing birds and their ancestor wild jungle fowl (JF). One-day male chicks (n = 150/line) were placed by line in environmentally controlled chambers and kept under the same industry-standard environmental conditions until d28. On d29, an 8-h daily cyclic HS (36°C) was applied to half of the chambers, which lasted until d55, while keeping the rest under thermal neutral (TN, 24°C) conditions. Jejunum tissues were collected for morphology assessment and molecular analysis of carbohydrate-, amino acid-, and fatty acid-transporters. MRB exhibited the highest body weight (BW) followed by 95RAN under both conditions. HS decreased feed intake (FI) in MRB and 95RAN, which resulted in lower BW compared to their TN counterparts; however, no effect was observed in ACRB and JF. MRB showed a greater villus height (VH) to crypt depth (CD) ratio under both environmental conditions. Molecular analyses showed that glucose transporter (GLUT) 2, 5, 10, and 11 were upregulated in MRB compared to some of the other populations under TN conditions. HS downregulated GLUT2, 10, 11, and 12 in MRB while it increased the expression of GLUT1, 5, 10, and 11 in JF. GLUT2 protein expression was higher in JF compared to ACRB and MRB under TN conditions. It also showed an increase in ACRB but no effect on 95RAN and MRB under HS conditions. ACRB exhibited greater expression of the EAAT3 gene as compared to the rest of the populations maintained under TN conditions. HS exposure did not alter the gene expression of amino acid transporters in MRB. Gene expression of CD36 and FABP2 was upregulated in HS JF birds. Protein expression of CD36 was downregulated in HS JF while no effect was observed in ACRB, 95RAN, and MRB. Taken together, these data are the first to show the effect of HS on jejunal expression of nutrient transporters in three broiler populations known to represent 70 years of genetic progress in the poultry industry and a Red Jungle Fowl population representative of the primary ancestor of domestic chickens.